Pendampingan Optimalisasi Pengelolaan Administrasi Badan Usaha Milik Desa (BUMDes) Untuk Mewujudkan Desa Mandiri Di Desa Grogol Kecamatan Grogol Kabupaten Kediri - Permadi, Candra (Welfare : Jurnal Pengabdian Masyarakat, 2023)
The village is the spearhead of Indonesia's development. With the issuance of laws that offer power to the village government in order to improve the welfare of the community, especially in rural areas, by optimizing existing resources, the village government needs to form village-owned enterprises (BUMdes). The goal of BUMdes is to improve the village economy and increase community efforts in managing the village's economic potential. However, in reality, not a few villages fail to run their businesses due to a lack of human resources in managing the BUMdes. Therefor, it is felt that there is a need for BUMdes management assistance in an effort to optimize BUMdes management and create an independent village. This devotional journal analyzes the optimization of the management of village-owned enterprises (BUMdes) to create an independent village. The results of the journal show that administrative management has begun to be organized with the help of application applications, which provide many superior features that make it easy to report to the village office.